ASSESSMENT OF URBAN HEAT ISLAND IN KADUNA METROPOLIS BETWEEN 2000 AND 2018 - Mande, Hosea Kato; Abashiya, Osayi Deborah (FUDMA JOURNAL OF SCIENCES, 2021)
Urbanization is a major event in human history and there is no doubt the world is urbanizing rapidly and this is resulting in changes in temperature. This research aims is to identify changes in land surface temperature (LST) between 2000 and 2018. The technique used is the Landsat TM. The result of the land cover classification revealed a +15.93% increase in built-up areas, -27.21% decrease in vegetative cover, +11.19% increase in bare land and +0.09 increase in water bodies between 2000 and 2018. NDVI analysis showed a +0.02 and +0.17 increase in the maximum and minimum range and a +2.16 and -7.76 increase and decrease in maximum and minimum temperature respectively for LST. The finding revealed that the repelling of vegetative cover by built-up is an evidence of rapid urbanization taking place in Kaduna metropolis and a major driver of UHI in Kaduna metropolis. Conclusively, there is a correlation between the various land covers of study i.e built-up, vegetative cover, bare land and water body and LST in Kaduna metropolis between 2000 and 2018. Likewise, urban development has a major impact on urban climate particularly in the increase in land surface temperature which in turn contributes to the development of urban heat. This is true because changes in urban land cover tend to alter the spectral signature and emissivity of the urban surface as observed using remote sensing. The researcher suggests further studies should focus on the assessment of UHI under different land cover and micro-climate in Kaduna metropolis.